Security market - Кочетова, Тетяна Іванівна (My University, 2018)
The aim of this work is to consolidate, deepen and systematization of scientific knowledge and practical skills of students on investment, as a result, of studying the discipline "securities Market". Aim and scope of the work to determine its following problems: the skills of finding and attracting information necessary for making investment decisions; the consolidation of skills to make informed decisions in conditions of uncertainty and risk, contingency, situational approach to the development of alternative investment options; the development of calculation methods using computer packages of applied programs.

Метою цієї роботи є консолідація, поглиблення та систематизація наукових знань та практичних навичок студентів з інвестицій, в результаті вивчення дисципліни "Ринок цінних паперів". Мета та обсяг роботи для визначення наступних проблем: навички пошуку та залучення інформації, необхідної для прийняття інвестиційних рішень консолідація навичок приймати обґрунтовані рішення в умовах невизначеності та ризику, непередбаченої ситуації, ситуаційного підходу до розробки варіантів альтернативних інвестицій; розробка методів розрахунку з використанням комп'ютерних пакетів прикладних програм.
Ринок цінних паперів
Keywords: securities portfolio; management; investment instruments; securities; портфель цінних паперів; цінні папери; інвестиційні інструменти; менеджмент